Методологічні основи та практика бюжетного контролю в стратегії управління будівельної організації - Іщенко, Т. М. (Ways to Improve Construction Efficiency, 2012)
The article explores the fundamentals implementation in construction companies controlling the flow of investments to improve the quality and efficiency of the management of their financial activity and optimize financial results.